Methodological approaches for researching the development of sports tourism in Ukraine - Mozolev, O. (Journal of Education, Health and Sport, 2023)
The article describes the concept of sports tourism. It was found that sports tourism is a type of active recreation, which is carried out by traveling along a route, testing one's own physical strength, moving on foot or on skis, bicycles or watercraft. To reveal methodological approaches to the study of the problems of the development of sports tourism in Ukraine. The importance of sports tourism for human development has been established. Its main features that distinguish sports tourism from other types of tourism are characterized. It was established that the most popular types of sports tourism in Ukraine are: hiking, water, cycling, speleological and ski tourism. Each type of sports tourism is characterized. The current state of sports tourism in Ukraine is analyzed. The prospects of its development in Ukraine are determined, the most popular regions for the development of certain types of sports tourism are given. The priority directions for the development of sports tourism in Ukraine have been identified. It has been established that by realizing their own physical capabilities, overcoming obstacles, adapting to new conditions and surroundings, tourists get physical and moral satisfaction from this type of recreation.